PHYLOGENETIC ANALYSIS OF ROBUSTA COFFEE (Coffea Canephora PIERRE EX FROCHNER) BASED ON MORPHOLOGICAL CHARACTERISTIC AND CLASS PROXIMITY - Nurmayanti, Sri; Tahir, Muhammad; Indrawati, Wiwik; Mahhendra, Bawon; Sari, Resti Puspa Kartika (Jurnal Agrotek Tropika, 2025)
In Indonesia, the most commonly cultivated type of coffee is Robusta coffee. Robusta coffee is a polyclonal plant, so its production can be increased by planting several superior clones in an area. One way to increase Robusta coffee production is by planting several superior clones in one area, because Robusta coffee is a polyclonal plant. The research was conducted by identifying the morphological characteristics of Robusta coffee. This is to see the relationship between Robusta coffee clones that have not been certified and clones that have been certified. The goals of this research were: 1) to knowing the morphology differences of Robusta coffee clones; 2) to knowing the proximity of Robusta coffee clone classes that have not been certified to those that have been certified; 3) Get a new clone of Robusta coffee. The research was conducted in a coffee plantation in Muara Baru, Kebun Tebu, West Lampung, Lampung. A Randomized Block Design (RBD) was used in this study and grouped by repetition. Observation of coffee morphological characters was carried out based on International Plant Genetic Resources Institute (IPGRI) coffee descriptor guidelines.. Morphological relationships are presented in the form of dendograms which are analyzed using the single link method. The results showed differences in the morphology of Robusta coffee clones. The Parabola clone has a different plant appearance from other clones, such as: large stems, large and long branches resembling a parabola. The Korolla 1, Korolla 3, Korolla 4, Sidokayo and Bagio clones have rounded and full flower buds. There is a relationship between certified and uncertified clones, namely the Sidokayo clone and Korolla 1 clone, the Tugu Sari clone and Sidokayo clone with Korolla 1 clone, and the Parabola clone with Korolla 4 clone. The Bagio clone has no affinity with any clone, so it can become new superior clone.